2021
DOI: 10.1101/2021.11.07.467597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sonogenetic stimulation of the brain at a spatiotemporal resolution suitable for vision restoration

Abstract: Remote, precisely controlled activation of the brain is a fundamental challenge in the development of brain-machine interfaces providing feasible rehabilitation strategies for neurological disorders. Low-frequency ultrasound stimulation can be used to modulate neuronal activity deep in the brain1–7, but this approach lacks spatial resolution and cellular selectivity and loads the brain with high levels of acoustic energy. The combination of the expression of ultrasound-sensitive proteins with ultrasound stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…At the same time, Cadoni et al utilized the same mediator MscL-G22s to make retinal ganglion cells and visual cortex neurons sensitive to ultrasound stimulation. The study confirmed the feasibility of MscL-G22s sonogenetics with low frequency ultrasound [43]. In addition, the results showed that higher frequency ultrasound at 2.2 MHz and 15MHz can also be used to improve the spatial resolution.…”
Section: A Large Conductance Mechanosensitive Ion Channel (Mscl) Chan...supporting
confidence: 69%
See 2 more Smart Citations
“…At the same time, Cadoni et al utilized the same mediator MscL-G22s to make retinal ganglion cells and visual cortex neurons sensitive to ultrasound stimulation. The study confirmed the feasibility of MscL-G22s sonogenetics with low frequency ultrasound [43]. In addition, the results showed that higher frequency ultrasound at 2.2 MHz and 15MHz can also be used to improve the spatial resolution.…”
Section: A Large Conductance Mechanosensitive Ion Channel (Mscl) Chan...supporting
confidence: 69%
“…On the other hand, the specificity of sonogenetic neural activation defined by eq (6) and eq (7) mainly relies on how the off-target effects were suppressed. Qiu et al (2020) and Cadoni et al (2021), showed that MscL-G22s based Sonogenetics are specific to targeted cells with 500kHz ultrasound stimulation below 0.45…”
Section: Selectivity and Specificity Of Sonogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these issues, sonogenetics approach was explored ( Ibsen et al, 2015 ). For example, a recent sonogenetics study expressed mechanosensitive ion channels (MscL) in the primary visual cortex of rodents; they achieved high spatial (∼100 μm) and temporal (<50 ms) resolution ( Cadoni et al, 2021 ). It has been known that the activation of 100 μm area in diameter would result in the restored visual acuity of 20/400 ( Palanker et al, 2020 ).…”
Section: Ultrasound Stimulation Of Retina and Visual Cortexmentioning
confidence: 99%
“…It has been known that the activation of 100 μm area in diameter would result in the restored visual acuity of 20/400 ( Palanker et al, 2020 ). The increased sensitivity of neuronal cells to UST was observed by heterogeneously expressed MscL, which increases Ca 2+ influx ( Cadoni et al, 2021 ). Considering these results, the sonogenetic strategy may open a new door for the application of engineered mechanosensitive channels for vision restoration in blind patients.…”
Section: Ultrasound Stimulation Of Retina and Visual Cortexmentioning
confidence: 99%